Exceptional Heme Tolerance in Serratia plymuthica: Proteomic Insights into Oxidative Stress Adaptation in the Aedes aegypti Midgut - Sâmella da Hora Machado; Rívea Cristina Custódio Rodrigues; Maria Aparecida Aride Bertonceli; Analiz de Oliveira Gaio; Gabriela Petroceli-Mota; Ricardo de Souza Reis; Marília Amorim Berbert-Molina; Vanildo Silveira; Francisco José Alves Lemos (Life, 2025)
Serratia plymuthica, isolated from the midgut of Aedes aegypti, displays remarkable resilience to hemin, a toxic hemoglobin byproduct generated during blood digestion. This study explores its proteomic adaptations under oxidative stress induced by 5 mM hemin, mimicking midgut conditions. Growth assays demonstrated that S. plymuthica tolerated hemin concentrations ranging from 5 µM to 1 mM, reaching the stationary phase within approximately 10 h. Colonies exhibited morphological changes—darkened peripheries and translucent halos—suggesting heme accumulation and detoxification. Label-free quantitative proteomics identified 436 proteins, among which 28 were significantly upregulated—including universal stress proteins (USPs), ABC transporters, and flavodoxin—while 54 were downregulated, including superoxide dismutase and several ribosomal proteins. Upregulated proteins were associated with antioxidant defense, heme transport, and redox regulation, whereas downregulated proteins suggested metabolic reprogramming to conserve energy under stress. Functional enrichment analysis revealed significant alterations in transmembrane transport, oxidative stress response, and central metabolism. These findings suggest that S. plymuthica contributes to redox homeostasis in the mosquito gut by mitigating reactive oxygen species (ROS) and detoxifying excess heme, supporting its role as a beneficial symbiont. The observed stress tolerance mechanisms may influence mosquito physiology and vector competence, offering novel insights into mosquito–microbiota interactions and potential microbiota-based strategies for vector control.